2011
DOI: 10.3399/bjgp11x601325
|View full text |Cite
|
Sign up to set email alerts
|

Screening for sickle cell and thalassaemia in primary care: a cost-effectiveness study

Abstract: BackgroundHaemoglobinopathies, including sickle cell disease and thalassaemia (SCT), are inherited disorders of haemoglobin. Antenatal screening for SCT rarely occurs before 10 weeks of pregnancy. AimTo explore the cost-effectiveness of offering SCT screening in a primary care setting, during the pregnancy confirmation visit. Design and settingA model-based cost-effectiveness analysis of inner-city areas with a high proportion of residents from ethnic minority groups. MethodComparison was made of three SCT scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 14 publications
(10 reference statements)
0
18
0
Order By: Relevance
“…Four papers examined exercise and weight loss, 386,400,427,428 and there were two papers in each of the following topic areas: CVD, 298,429 NHS Health Checks, 149,150 and health checks for people with learning disabilities. 158,161 The other three papers examined sickle cell screening, 430 breast screening 210 and smoking cessation. 380 Generally there was little substantial evidence to make general conclusions about the cost-effectiveness of health improvement interventions in general practice.…”
Section: Evidence On Cost-effectivenessmentioning
confidence: 99%
“…Four papers examined exercise and weight loss, 386,400,427,428 and there were two papers in each of the following topic areas: CVD, 298,429 NHS Health Checks, 149,150 and health checks for people with learning disabilities. 158,161 The other three papers examined sickle cell screening, 430 breast screening 210 and smoking cessation. 380 Generally there was little substantial evidence to make general conclusions about the cost-effectiveness of health improvement interventions in general practice.…”
Section: Evidence On Cost-effectivenessmentioning
confidence: 99%
“…Bryan et al [74] however, has disregarded this theory, suggesting in hepatocellular carcinoma, a secondary molecule must be present in order to trigger the expression of hepcidin. One example, in particular, is thought to occur through the activation of STAT3 by the inflammatory cytokine IL-6.…”
Section: Jak-stat Pathwaymentioning
confidence: 99%
“…One example, in particular, is thought to occur through the activation of STAT3 by the inflammatory cytokine IL-6. Throughout their study, Bryan et al [74] found that the binding of IL-6 to its receptor, lead to the activation of JAK2, which in turn, phosphorylates STAT3. STAT3 was then translocated to the nucleus and bound to its binding motif at -64/-72 within the promoter region of hepcidin.…”
Section: Jak-stat Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Also in this month's journal, Bryan et al present the economic analysis of early screening for thalassaemia and haemoglobinopathies. 5 Previous papers from this study had established that threequarters of all women consulted for pregnancy before 10 weeks' gestation, but that fewer than 5% had received screening by that time. 6 Introducing two different models where screening was offered at the first consultation, and before the midwife booking consultation, increased the proportion screened by 10 weeks from 2% to 24% and 28%.…”
Section: Economics Of Screeningmentioning
confidence: 99%